Види діяльності в обліку та звітності підприємств в умовах переходу до інформаційної економіки - Ілляшенко, Катерина Володимирівна; Илляшенко, Екатерина Владимировна; Illiashenko, Kateryna (ТДАТУ, 2017)
UK: статті розглянуто основні аспекти інформатизації суспільства та досліджено вплив новітніх інформаційних технологій на вітчизняну економіку. Проаналізовано трактування поняття «інформа- ція» та її вплив на прийняття ефективних управлінських рішень. Досліджено різні види діяльності в бухгал- терському обліку та звітності підприємств в умовах глобальної інформатизації, запропоновано застосовува- ти новий вид діяльності «інформаційна діяльність». Доведено, що для формування фінансового результату від інформаційної діяльності необхідно впровадити нові рахунки бухгалтерського обліку «інформаційні доходи» та «інформаційні витрати». EN: The purpose of this article is a scientific research of the activities of the enterprises in the condi- tions of Informatization of society and finding new kinds of activities - «information activity». In the conditions of transformation of modern economy to the continuous introduction of digital technology and instant information dissemination is very important is an upgraded reflection of the activities of enterprises At the present stage methodology national provisions (standards) of accounting there are three types of activities: operating, financial, investment. There is a need to introduce of new concepts such as information costs and information returns as well as providing them with new definitions. Information becomes an increasingly important lever in all areas of the enterprise. Still the information as a resource, not reflected in accounting. However, the information needs to be highlighted as a separate category of ac- counting and be recognized in the financial statements of companies. Information activities in the accounting and reporting enterprises should be displayed according to the modern changes that are happening in the world of rampant information. It is necessary to introduce concepts such as «income information» and «information costs». The article proposes an interpretation of these concepts and the example reflect them in accounting through the use of new accounts. The transformation of the modern economy in the information requires changes in methodology of accounting and reporting, and requires further in-depth studies. The study proposed to reflect the results of information activities in a separate section in the statements. This section may be called «Income and expense information activities». Thus, the structure of the report and the methods of filling does not undergo significant changes, and the new section will also be supported by manual and algorithm build.
Activities in accounting and reporting of enterprises in conditions of transition to informational economy
Keywords: інформація; облік; звітність підприємств; види діяльності; доходи; витрати; фінансовий результат; іnformation; records; reporting; activities; income; expenses; financial result